Phylogeography of the endangered sand dune whiptail lizard Glaucomastix abaetensis (Dias, Rocha & Vrcibradic, 2002) with the description of a new species - Rosário, Igor Rios Do; Dos Santos, Rodrigo Marques Lima; Arias, Federico; Rocha, Carlos Frederico Duarte; Dos Reis Dias, Eduardo José; de Carvalho, Celso Morato; Rodrigues, Miguel Trefaut (Zootaxa, 2019)
Several species of Glaucomastix lizards have been described over the past decade, most of these inhabit inland Brazil. Glaucomastix abaetensis is a threatened whiptail endemic to Brazilian coastal “restinga” (sandy habitats) from Bahia State to Sergipe, with a distribution limited by riverine barriers. In order to investigate the differentiation and relationships in G. abaetensis, we integrated phylogeographic analysis, Bayesian species delimitation and morphological data to detect geographical patterns and historical events responsible for its present distribution. We recovered two highly divergent clades along its range, one of them unnamed. Glaucomastix itabaianensis sp. nov. has a a yellowish green tail, 13–16 scales in the lateral flank, 22–33 scales around tail, 28–35 femoral pores and usually four supraocular scales with the smaller one disposed posteriorly. Our results retrieved the monophyly of Glaucomastix, with G. venetacauda and G. cyanurus being sister species to a clade formed by G. littoralis and G. abaetensis. Divergence between Glaucomastix abaetensis and the new species occurred roughly 2.39 Myr ago; posterior shallow genetic divergences occurred mainly in Pleistocene. Finally, we present data on the conservation of this clade of whiptail lizards.